Situation du partage des compétences législatives en matière de ressources naturelles au Canada - Rémillard, Gil (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1977)
With respect to the public domain, the British North America Actof 1867 established a division of authority which is relatively simple in principle: residuary interest in property belongs to the Provinces while the Federal authority has no more than the power of exception. From this principle which is derived principally from article 109 of the 1867 Act, we can say that the Provinces have authority to legislate on questions affecting natural resources. However, the Canadian Parliament can also legislate on questions affecting natural resources. This is derived from either express authority granted it or from implied authority. In effect, the majority of the authority which permits the Canadian Parliament to legislate in matters affecting natural resources is derived either directly or indirectly from the application of its trenching power.The introductory clause of article 91 of the 1867 Act is an important source of the Federal authority over natural resources. Through the application of the national dimension theory, Ottawa has assumed control over atomic energy, off-store mineral resources, water management, and the expropriation of provincial lands. Moreover, through the application of emergency powers, Parliament could eventually legislate on a considerable number of subjects related to natural resources.Also, a number of the Federal Government's enumerated powers permit the control authority to legislate on questions of natural resources. The principle examples of this are its authority over the public debt and property, commerce, taxation, navigation, fisheries, Indians, the authority granted it by article 92(10c), and article 108 of the 1867 Act. One must thus conclude that by judicial interpretation, the Federal government has gained concurrent authority over natural resources through the application of the principle of Federal preponderance in case of conflict.